REVISITING ENVIRONMENTAL SOCIOLOGY: ITS BEGINNING TO PRESENT STATE. - Md. Sayed Uddin, Uddin; Adam Andani, Mohammed (International Journal of Advance Research, 2011)
Sociology has not appeared as one of the core environmental sciences like geography, even though it is one of the social and human sciences. It makes important contribution considering the interest shown by the founders like Durkheim, Weber and Marx in the relationship between human societies and their environment. The direct effect of human activity on the natural world which influences the social realm raised concerns at practical and theoretical levels with issues of hazard, risk and the environment. This desk top case study therefore reviewed literature on the concept and principles and the ways in which environmental matters are discussed within everyday life and sociology. This paper deals with themes of environmental sociology‟s key concepts and debate on the role of classical theorists in the discipline. It specifically focused on the larger theoretical and conceptual challenge on how the discipline of sociology can usefully address questions of nature and the physical environment and what would this in turn mean for sociology.